Aligning Environmental Policy and Green Marketing: A Critical Review from the Indian Context (International Journal of Environmental Sciences, 2025)
As emerging economies pursue rapid industrial growth, balancing economic development with environmental sustainability has become increasingly critical for millions of businesses and consumers. India's green marketing landscape presents a compelling case study of both challenges and opportunities in this balance. This paper critically examines Indian policy frameworks—including national bans on single-use plastics, Extended Producer Responsibility, the Ecomark eco-labelling scheme, and Corporate Social Responsibility mandates—that directly influence how businesses approach environmental marketing and how consumers respond to green products.Drawing on systematic secondary data analysis and comparative policy evaluation, this study applies institutional theory and stakeholder theory to examine how these policy instruments drive corporate environmental responsibility while shaping stakeholder perceptions and market dynamics. The findings reveal that despite strong regulatory intentions, institutional gaps, implementation challenges, and disconnects between consumer expectations and business capabilities significantly limit the effectiveness of green marketing as a sustainable business strategy in India.The research contributes theoretically-grounded recommendations for institutional strengthening, enhanced multi-stakeholder engagement, and innovative policy mechanisms that address the real-world constraints faced by businesses of different sizes and consumers across diverse socioeconomic contexts. By addressing the institutional and market failures identified in this analysis, India can develop a more robust green marketing ecosystem that delivers measurable environmental outcomes while providing sustainable competitive advantages for businesses.